ENHANCING THE LEARNING OF BASIC CONCEPTS IN BIOLOGY WITH THE UTILIZATION OF MOBILE BIO-APPS AMONG BIOLOGY STUDENTS IN COLLEGE OF EDUCATION, IKERE, EKITI STATE, NIGERIA - Oladosu, Adebiyi Toyosi (PEOPLE: International Journal of Social Sciences, 2020)
The study examined the utilization of a mobile application that is biology-based in the learning of some basic concepts among NCE II students in the Department of Biology, College of Education, Ikere, Ekiti State, Nigeria. Among all the NCE Part II students which constituted the population, 60 students were purposively chosen and eventually randomly sampled into individualized Bio-Apps and collaborative Bio-Apps of 30 students each. These Bio-Apps groups have functional smart phones and their smartphones have biology dictionary downloaded on them. The third group of 30 students are of the traditional classroom and were randomly selected from the population. In all, 90 students formed the sample for this study. All the groups were exposed to the same instructional contents in BIO 214 (Plant Pathology). The individualized mobile Bio-Apps group was made to check basic concepts in plant pathology from the biology dictionary on their smart phones and participated as the classes progressed. The collaborative Bio-Apps group was made to check those basic concepts in plant pathology from their mobile Bio-Apps and collaborated among themselves in clusters while the classes progressed; while the traditional group was without mobile bio-apps and taken through traditional instructional strategy. Standardized Biology Achievement Test was administered on the three groups. Two research questions and two hypotheses were raised and answered descriptively. The results from the analyses show that students in Mobile Bio-Apps groups performed better that their counterparts in traditional class. Meanwhile, students in the collaborative performed than those in the individualized mobile bio-app. It was therefore recommended among others that, Mobile Bio-App should be integrated into students’ learning of basic concepts in biology in a collaborative form so as to avoid distraction in using the mobile phones for something else other the learning while the teaching-learning lasted.